Revisiting the Synod of Dordt (1618-1619) - Goudriaan, Aza 1969-; Lieburg, F. A. van 1967- (Leiden Boston Brill, 2011)
Gisbertus Samuels, a Reformed minister sentenced by the Synod of Zeeland in 1591 for his opinions on predestination / Fred van Lieburg -- Defense or deviation? : a re-examination of Arminius' motives to deviate from the 'mainstream' Reformed theology / William den Boer -- Philosophy and the Synod of Dordt : Aristotelianism, humanism, and the case against Arminianism / Henri A. Krop -- The Synod of Dordt on Arminian anthropology / Aza Goudriaan -- The petitions of 'a supposed prophetesse' : the Lübeck letters of Anna Walker and their significance for the Synod of Dordt / Jürgen Beyer, Leigh T.I. Penman -- A distorting mirror : the Hales and Balcanquahall letters and the the Synod of Dordt / Anthony Milton -- James Ussher's influence on the Synod of Dordt / Jonathan D. Moore -- "The canons of the Synod had shot off the advocate's head" : a reappraisal of the Genevan delegation at the Synod of Dordt / Nicolas Fornerod -- On the Maccovius affair / Willem J. van Asselt -- Popular and catholic : the Modus docendi of the Synod of Dordt / W. Robert Godfrey -- "O, ye women, think of thy innocent children, when they die young!" : the Synod of Dordt (first head, article seventeen) between polemic and pastoral theology / Erik A. de Boer -- The drafting of the Synod of Dordt : a preliminary survey of early drafts and related documents / Donald Sinnema -- Imagining the Synod of Dordt and the Arminian controversy / Joke Spaans -- Ambivalent assessments of the Synod of Dordt by Dutch Contra-Remonstrants / Willem J. op 't Hof -- Making sense of schism / Joris van Eijnatten.
Proceedings of a conference held Apr. 6-7, 2006 in Dordrecht, Netherlands. - Includes bibliographical references and indexes. - Description based on print version record
Online-Ausg.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Synod of Dort <(1618-1619> -- Congresses -- Synod of Dort; Synod of Dort; RELIGION ; Christian Theology ; Ecclesiology; Conference papers and proceedings; Electronic books -- Conference proceedings; Konferenzschrift